Financial assessment of performance in the hotel industry - Nunes, C. (2017)
This paper aims to increase the knowledge on the financial methods of performance assessment used in the hotel industry, and is based on a review of empirical studies already performed. The reviewed articles allow us to conclude that the financial measures have a significant weight in the hotel industry performance assessment, but they should be complemented by other non-financial measures that consider the particularities of this industry, as well as the specific characteristics of hotel service. As this paper’s main limitation we state the reduced number of studies found on the hotel industry, thus suggesting the need for further research on the performance assessment systems effectively used by the sector, as well as the identification of possible contingency variables that justify the use of specific measures in specific hotels.